2010
DOI: 10.1186/1471-2199-11-14
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors Elk-1 and SRF are engaged in IL1-dependent regulation of ZC3H12A expression

Abstract: BackgroundMCPIP is a novel CCCH zinc finger protein described as an RNase engaged in the regulation of immune responses. The regulation of expression of the gene coding for MCPIP - ZC3H12A is poorly explored.ResultsHere we report that the proinflammatory cytokine IL-1β rapidly induces the synthesis of MCPIP in primary monocyte-derived macrophages and HepG2 cells. This up-regulation takes place through the MAP kinase pathway and following activation of the transcription factor Elk-1. Using a ZC3H12A reporter co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 22 publications
2
53
1
Order By: Relevance
“…Several inflammatory factors, such as LPS, TNF-a, MCP-1, and IL-1b, can induce MCPIP1 expression, which is mediated by both the NF-kB and ERK pathways (7)(8)(9)(10)14). In this study, we found upregulated mRNA expression of TNF-a, IL-6, and MCP-1 in HCV-infected Huh7.5 cells.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Several inflammatory factors, such as LPS, TNF-a, MCP-1, and IL-1b, can induce MCPIP1 expression, which is mediated by both the NF-kB and ERK pathways (7)(8)(9)(10)14). In this study, we found upregulated mRNA expression of TNF-a, IL-6, and MCP-1 in HCV-infected Huh7.5 cells.…”
Section: Discussionsupporting
confidence: 56%
“…Its expression can be induced by other proinflammatory molecules, such as TNF-a, IL-1b, and LPS (6)(7)(8)(9)(10). MCPIP1 mainly contains a highly conserved Nedd4-BP1, YacP nuclease/deubiquitinase (NYN/DUB) domain with intrinsic RNase and DUB activities at the N terminus, a single CCCH-type ZF domain with RNA-binding potential in the middle region, and a proline-rich (PRR) domain for protein oligomerization at the C terminus (9,11,12).…”
Section: H Epatitis C Virus (Hcv) the Only Member Of The Genusmentioning
confidence: 99%
“…In primary hepatocytes, MCPIP1 mRNA is induced synergistically by TNF and IL-17 (10). Transcriptional induction by IL-1␤ has been demonstrated to involve the NF-B and ERK pathways and Elk-1 transcription factor (33,34). Most recently, post-transcriptional mechanisms controlling MCPIP1 have been reported that act through the IB kinase complex, which controls ubiquitination and degradation of MCPIP1 protein and through MCPIP1 itself, which controls degradation of its own mRNA (35).…”
mentioning
confidence: 99%
“…However, NF-κB is more than just a transcription factor and should be rather regarded as an universal switch in the innate and acquired immune reactions (reviewed in Hoffmann & Baltimore, 2006). Other typical transcription factors used by inflammatory mediators include AP-1, (activator protein-1, usually a hetero-dimer of c-Fos/c-Jun (Hattori et al, 1993)), STAT (signal transducer and activator of transcription known in six isoforms numbered STAT1 -STAT6 (Baumann, 2003;Heinrich et al, 2003;Sehgal, 2008), C/EBP (CAAT enhancer binding protein, occurring in four isoforms (Huang & Liao, 1994) and Elk-1 (Kasza et al, 2010) (for comprehensive list of earlier references see Ray et al, 1990;Koj, 1996, Ruminy et al, 2001. The interactions between the various TFs that compete for binding sites in the promoter regions of various genes are highly complex and regulation of IL-6 expression, described first by Sehgal et al, (1995) and later by van den Berghe et al, (2000), may provide some useful information.…”
Section: Inflammation Control: Components and Rulesmentioning
confidence: 99%